PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN JERSEY SUBLIM PADA TOKO SYARIF JERSEY KABUPATEN TANGERANG - Muhamad Ugi; Dewi Ningsih (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study was to determine the effect of product quality and price on purchasing decisions. The research method used is quantitative descriptive method. The sampling technique used the rao purba formula, so that a sample of 96 respondents was obtained. While the primary data collection technique is through a questionnaire which is processed using the SPSS Version 27 application system. The data analysis method uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The result of this study is that product quality has a positive and significant effect on purchasing decisions with a coefficient of determination of 66.5% and hypothesis testing t count> t table or (13.646> 1.98552) or significance 0.000 <0.05. The price has a positive and significant effect on purchasing decisions with a coefficient of determination of 74.2% and the hypothesis test obtained t count> t table or (16,457> 1.98552) or a significance of 0.000 <0.05. the effect of product quality and price simultaneously has a positive and significant effect on purchasing decisions with the regression equation Y = 2,680 + 0,240X1 + 0,623X2. The coefficient of determination is 72.2%, the hypothesis test obtained the value of F count> F table or (158,022> 2.70). Keywords: Product quality, Price, Purchase Decision